Prediction of in-situ dry unit weight considering chamber boundary effects on lateritic soils using Panda® penetrometer. Issue 4 (21st April 2022) - Gansonré, Y.; Breul, P.; Bacconnet, C.; Benz, M.; Gourvès, R.
ABSTRACT: Lateritic soils are the most common materials in tropical areas and widely used in pavement engineering. In fact, in these areas, pavement compaction control is generally performed through the measurements of the in-situ unit weight of the soils. However, these methods are time-consuming and expensive. So, in many countries, methodology based on the use of the dynamic penetrometer has become widespread for rapid and less costly control of pavement quality. This methodology is efficient but requires calibration between the cone resistance and the dry unit weight. Due to the specific nature of lateritic soils, to their assumed wide variability and probably to other reasons, no calibration has actually been performed in-situ for these soils. The calibrations performed until now, has been carried out using chambers in the laboratory. This process provides some bias for the prediction of in-situ dry unit weight, due to the chamber boundary effects which affect cone resistance. This paper proposes a methodology that consists of testing the soils in-situ and in the laboratory, studying cone resistance according to compaction parameters in order to estimate the boundary effects and to propose a model to take them into account when predicting in-situ dry unit weight.